Minimization of Symbolic Tree Automata - Veanes, Margus (LICS, 2016)
Symbolic tree automata allow transitions to carry predicates over rich alphabet theories, such as linear arithmetic, and therefore extend finite tree automata to operate over infinite alphabets, such as the set of rational numbers. Existing tree automata algorithms rely on the alphabet being finite, and generalizing them to the symbolic setting is not a trivial task. In this paper we study the problem of minimizing symbolic tree automata. First, we formally define and prove the basic properties of minimality in the symbolic setting. Second, we lift existing minimization algorithms to symbolic tree automata. Third, we present a new algorithm based on the following idea: the problem of minimizing symbolic tree automata can be reduced to the problem of minimizing symbolic (string) automata by encoding the tree structure as part of the alphabet theory. We implement and evaluate all our algorithms against existing implementations and show that the symbolic algorithms scale to large alphabets and can minimize automata over complex alphabet theories.